The structure, processes, and outcomes of stroke rehabilitation in Ghana: A study protocol - Yarfi, Cosmos; Nyante, Gifty Gyamah; Rhoda, Anthea (Frontiers in Neurology, 2022)
Background Conventional and complementary treatments are often used in rehabilitation for persons with stroke. The conventional treatment makes use of medications, physiotherapy, occupational, speech, and diet therapies, while the complementary treatment makes use of homeopathy, naturopathy, massage, and acupuncture. The structure, process, and outcomes of stroke rehabilitation using conventional or complementary treatments have not been empirically investigated in Ghana. Aims This study aims to investigate the structure, process, and outcomes of stroke rehabilitation at the Korle Bu Teaching Hospital (KBTH) in Accra and Kwayisi Christian Herbal Clinic (KCHC) in Nankese-Ayisaa, Ghana, and to explore the experiences of persons with stroke. Methods This study involves a mixed methods approach. This study will utilize three study designs, namely, cross-sectional, hospital-based cohort, and qualitative exploratory study designs. The objectives of the study will be achieved using three phases, namely, phase one will recruit health professionals and gather information on the structure and process of stroke rehabilitation at a conventional and complementary hospital using adapted questionnaires; phase two will determine the outcomes of stroke patients attending a conventional and complementary hospital facility at baseline, 2-, 3-, and 6-month follow-up using outcome measures based on the International Classification of Functioning, Disability and Health (ICF) model; and phase three will explore the experiences of stroke patients who use complementary or conventional treatment using an interview guide. Data analysis IBM SPSS Statistics Version 27 will be used to analyze the data using descriptive and inferential statistics. Repeated measures of ANOVA will be used to determine the differences between variables at baseline, 2-, 3-, and 6-month post-stroke. The qualitative data will be transcribed and entered into Atlas Ti version 9.0. The data will be coded and analyzed using thematic areas that will be generated from the codes. Conclusion The study protocol will provide a comprehensive overview of the structure, process, and outcomes of stroke rehabilitation in Ghana, incorporating both conventional and complementary treatment and rehabilitation into the stroke recovery journey. It will also inform clinical practice, with new insights on the experiences of stroke patients based on their choice of rehabilitation pathway.